The Relevance of Chitonga as a Regional Language of Instruction in the Multilingual Schools of Livingstone Urban in Southern Province of Zambia (British Journal of Multidisciplinary and Advanced Studies, 2024)
The purpose of the study was to find out the relevance of Chitonga as a regional language of instruction from Grade 1 to 4 in multilingual schools of Livingstone. The study objectives were, to assess how teachers are teaching literacy to grade 1 to grade 4 using Chitonga in the multilingual classes of Livingstone and to establish the pedagogical challenges teachers face on the use of Chitonga as a language of instruction in Livingstone. The study used a phenomenological design on the population of Livingstone District. Data was collected using interview guide and classroom observation guide from three primary schools and sixteen (16) participants who included three (3) head teachers, twelve (12) grade 1 to 4 teachers (four (4) from each selected school) and one (1) official from the district education board. The findings revealed that teachers in Livingstone multilingual schools taught Literacy in Chitonga through translanguaging practices like translation and code switching. They also used flash cards, syllabic cards and talking walls. The findings also indicated that Chitonga was not the language of play in multilingual primary classrooms of Livingstone. It was also revealed that there were differences between the Chitonga spoken in Livingstone District and the one used in schools and books. Both teachers and pupils were not proficient in the standard Chitonga. The study concluded that Chitonga despite being the regional language, it was not relevant to the urban primary school learner of Livingstone town because the classrooms were multilingual hence translanguaging practices were used extensively. In the view of the findings, the study recommended that there should be training for primary teachers to teach in multilingual classrooms and schools need to buy more teaching and learning materials in Chitonga for primary schools to help teachers in multilingual classes.